Acute effects of insulin and insulin‐induced hypoglycaemia on carotid body chemoreceptor activity and cardiorespiratory responses in dogs. Issue 2 (2nd December 2022) - Baby, Santhosh M.; Zaidi, Faisal; Hunsberger, Gerald E.; Sokal, David; Gupta, Isha; Conde, Silvia V.; Chew, Daniel; Rall, Kristen; Coatney, Robert W.
Abstract : New Findings: What is the central question of this study? What are the effects of insulin and insulin‐induced hypoglycaemia on carotid body chemoreceptor activity in vivo and how do carotid body chemoreceptor stimulation‐mediated cardiorespiratory responses in beagle dogs compare during euglycaemia and insulin‐induced hypoglycaemia? What is the main finding and its importance? Intracarotid insulin administration leads to sustained increase in carotid body chemoreceptor activity and respiratory response with significant cardiovascular effects. Insulin‐induced hypoglycaemia exacerbated NaCN‐mediated carotid body chemoreceptor activity and respiratory response with enhanced cardiovascular reflex response. These findings suggest that insulin‐induced hypoglycaemia augments the carotid body chemoreceptors to initiate the adaptive counter‐regulatory responses to restore the normoglycaemic condition. Abstract: The carotid body chemoreceptors (CBC) play an important role in the adaptive counter‐regulatory response to hypoglycaemia by evoking the CBC‐mediated sympathetic neuronal system to restore normoglycaemia. Ex vivo studies have shown varied responses of insulin‐induced hypoglycaemia on CBC function, and several in vivo studies have indirectly established the role of CBCs in restoring normoglycaemia in both animals and humans. However, a direct effect of insulin and/or insulin‐induced hypoglycaemia on CBC activity is not established in animal models. Therefore, the aim of this study was to evaluate in vivo effects of insulin and insulin‐induced hypoglycaemia on CBC activity and cardiorespiration in a preclinical large animal model. The carotid sinus nerve (CSN) activity and cardiorespiratory responses to sodium cyanide (NaCN; 25 µg/kg) were compared before (euglycaemic) and after (hypoglycaemic) intracarotid administration of insulin (12.5–100 µU/dogs) in beagle dogs. Insulin administration increased CSN activity and minute ventilation ( V ̇ $\dot V$ E ) with significant ( P  < 0.0001) effects on heart rate and blood pressure. Insulin‐mediated effects on CSN and cardiorespiration were sustained and the change in V ̇ $\dot V$ E was driven by tidal volume only. Insulin significantly ( P <  0.0001) lowered blood glucose level. NaCN‐mediated CSN activity and V ̇ $\dot V$ E were significantly ( P  < 0.0001) augmented during insulin‐induced hypoglycaemia. The augmented V ̇ $\dot V$ E was primarily driven by respiratory frequency and partially by tidal volume. The cardiovascular reflex response mediated through CBC stimulation was significantly ( P  < 0.0001) exacerbated during insulin‐induced hypoglycaemia. Collectively, these results demonstrate direct effects of insulin and insulin‐induced hypoglycaemia on CBC chemosensitivity to potentiate CBC‐mediated neuroregulatory pathways to initiate adaptive neuroendocrine and cardiorespiratory counter‐regulatory responses to restore normoglycaemia.